If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) = 2 + -1x Reorder the terms: 2(-2 + x) = 2 + -1x (-2 * 2 + x * 2) = 2 + -1x (-4 + 2x) = 2 + -1x Solving -4 + 2x = 2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -4 + 2x + x = 2 + -1x + x Combine like terms: 2x + x = 3x -4 + 3x = 2 + -1x + x Combine like terms: -1x + x = 0 -4 + 3x = 2 + 0 -4 + 3x = 2 Add '4' to each side of the equation. -4 + 4 + 3x = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 2 + 4 3x = 2 + 4 Combine like terms: 2 + 4 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| x/6=-2 | | 2-(-8)= | | 3(x+6)-2=15 | | 9+9c=9 | | 5x-4=3x+3x+8 | | p+10+(p-19)+2*p=699 | | p+10+p+19-2p=699 | | 3x+8-2x=-24 | | 11x-6=3x+26 | | 4x^2-11x+5=-2x+3 | | 6x^2-7x-49=0 | | y=3x^2+12x+5 | | 350=s+s+20 | | x^2+x+18=-8+4 | | x^2-6x+18=10 | | 4(b-2)=2(5-h) | | (4x-1)2=11 | | -.166(x-18)+0.5(x+2)=x+12 | | y=x^2+18+95 | | 8x=4x+4 | | 3x+48=6x+6 | | x^2-9x+16=8 | | .01x-7=13 | | 3.56+458+49.6= | | 16(2x-5)=4(8x+1) | | 4+13p-1=8p+53-5p | | 400-6.59= | | 4x^2+13+9=0 | | x^2+5x-27=9 | | 5s+12s=85 | | -9.8x=68.6 | | y=-x^2+3x+10 |